# College AlgebraWhat is an equivalent expression for the following equation without using parentheses? Explain Please. 1. -(x+2) 2.- (5x +2y +8)

Matthew Fonda | Certified Educator

You can think of that negative sign in front of the parenthesis as multiplying everything inside them by -1, then use the distributive property.

1. -(x + 2) = -1 * (x + 2) = -1*x + -1*2 = x - 2

2. -(5x + 2y + 8) = -1 * (5x + 2y + 8) = -1*5x + -1*2y + -1 * 8 = -5x - 2y - 8

kanishkporwal | Student

1. -(x+2)

2.- (5x +2y +8)

while opening paranthesis you need to remember that when you multiply the number outside the paranthesis into it then you first multiply the number and then you multiply the signs

always remember

- * - = +

- * += -

+ * +=+

just hope this helps.

Also if you ever get stuck, you can find some online algebra 2 help at tutorvista.com

moocow554 | Student

number one could be either -x + 2, or X-2

If you plug a number, 8 for example in place of x, you will get

-x+2...-8+2=-6

x-2...8-2=6

Number two could be. -5x-2y-8, or

If you plug a number, 8 for example in place of x, and 7 for example in place of y, you would get

-5x-2y-8...-5(8)-2(7)-8 = -62

toby14 | Student

Take the negative sign on the outside and multiply the numbers inside the parenthesis by negative one.

1. -(x+2): You multiply -1*x making that -x, and then by 2 making that -2. Therefore, your answer= -x-2

2. -(5x+2y+8): Same concept. multiply -1 by 5x making it -5x, then multiply it by 2y making that -2y, and then multiply it by 8 making that -8. Your answer will come out to= -5x-2y-8.

Hope this helps!